Penerapan Arsitektur Organik pada Bangunan Wisata Kuliner Lokal di Kabupaten Enrekang - Jumain, Aldiani; AS, Zulkarnain; Nuryuningsih, Nuryuningsih (TIMPALAJA : Architecture Student Journals, 2025)
In the field of architecture, the concept of organic architecture emphasizes environmental aspects and harmony between a building and its site. The four main characteristics of organic architecture implementation are creating unique buildings that express their relationship with nature both externally and internally, selecting materials that align with their natural properties to create harmony with the surrounding environment, ensuring building elements blend well together, and the ability to communicate the time, place, and purpose of the design. This study aims to investigate the application of organic architecture in culinary tourism as a way to showcase regional uniqueness through distinctive local cuisine. The research methods include field data collection on physical environmental conditions, literature review on culinary tourism from books, journals, theses, and online sources, as well as examination of precedent buildings. Data analysis was conducted using descriptive techniques with reference to organic architecture planning and design guidelines. The findings indicate that applying organic architecture in culinary tourism can strengthen a region’s identity and uniqueness by offering local dishes prepared by the community. Therefore, culinary tourism based on organic architecture plays a significant role in enhancing the potential of unique local tourism.